Sistem Informasi E-Learning Di SMA Negeri 1 Rantau Selatan Berbasis Web - Ayu Lestari Dalimunthe (Journal of Student Development Informatics Management (JoSDIM), 2022)
E-learning information system The rapid development of technology and information has influenced in various aspects of life including in the field of education. Therefore, educational institutions must be able to anticipate these developments by continuously striving for a program that suits the needs of students. conducting educational innovations, one of the educational innovations by implementing e-learning, Electronic Learning, is a new way of teaching and learning that uses electronic media, especially the internet as a learning system. The hope for the E-learning system in the future is the use of E-learning to be more effective along with the development of technology and learning methods used. The development of the E-learning system is also expected to not only take into account financial problems and profitability, but also pay attention to the psychological side of students and be able to accommodate the various personalities and ways of learning of each participant. Hopefully with this application, it can improve performance in the process of student data management and data search students needed anytime in SMA Negeri 1 Rantau Selatan.